Why do fiscal multipliers depend on fiscal positions? - Raju Huidrom; M. Ayhan Kose; Jamus Jerome Lim; Franziska Ohnsorge (Koç University-TÜSİAD Economic Research Forum (ERF), 2019)
The fiscal position can affect fiscal multipliers through two channels. Through the Ricardian channel, households reduce consumption in anticipation of future fiscal adjustments when fiscal stimulus is implemented from a weak fiscal position. Through the interest rate channel, fiscal stimulus from a weak fiscal position heightens investors' concerns about sovereign credit risk, raises economy-wide borrowing cost, and reduces private domestic demand. We document empirically the relevance of these two channels using an Interactive Panel Vector Auto Regression model. We find that fiscal multipliers tend to be smaller when fiscal positions are weak than strong.
Keywords: E62; H50; H60; 330; Fiscal multipliers; fiscal position; state-dependency; Ricardian channel; interest rate channel; business cycle